Applications of Microfluidics in Biomedical and Pharmaceutical Fields -An Overview - Stefna Varghese; Dr. Poonam Parashar; Dr. Pragya, (International Journal of Preventive Medicine and Health (IJPMH), 2025)
The precise manipulation of fluids at the microscale level within minuscule channels measuring tens to hundreds of micrometres is the subject of the multifaceted field of microfluidics. This technology has transformed the pharmaceutical industry by enabling miniaturised, high-throughput, and economical drug discovery, formulation, and delivery solutions. Creating sophisticated drug delivery systems like nanoparticles and liposomes has become far simpler because this method can precisely control fluid dynamics, enabling faster reaction kinetics and better drug encapsulation. Beyond drug formulation, microfluidic platforms enable disease modelling, toxicity assessment, and pharmacokinetic/pharmacodynamic analysis, providing a quick and efficient alternative to conventional techniques. In addition, devices like microfluidic chips combine several analysis processes into a single device with less reagent consumption and enhanced research encouragement. Furthermore, microfluidics is vital in personalised medicine and point-of-care diagnostics, offering rapid, more accurate testing for a customised treatment strategy. The increased use of microfluidics in pharmaceutical research is promising to facilitate faster drug discovery, enhance individualised medicine, and improve point-of-care diagnostic testing. This paper discusses the definition, importance, and uses of microfluidics in the pharmaceutical field based on its implications for the future of drug discovery and healthcare.